Knowledge and Experience of Bullying among Secondary Level Students in Kathmandu (Teacher Half-Yearly Journal, 2025)
Bullying is problematic human behavior that abuses others. There are different types of bullying. Among them, school bullying is common among students. It impacts overall physical, mental, and emotional health. The study aims to identify the knowledge and experience of bullying among students. A descriptive study was conducted among 145 respondents of class 12 students of one government and two institutional schools of Kathmandu district by using random sampling without replacement method. Results indicate that more than 90 percent (133) of respondents have the knowledge, and 22.62 percent of respondents have experienced bullying. The bivariate (Chi-square) analysis was used to examine the associations between variables. Sex is treated as an independent variable, and experience of bullying is treated as a dependent variable. The test showed that there was no association between sex and experience of bullying (p = 0.819 in 5% ∝ for 1 d.f). It is concluded that 10 percent of respondents did not know about bullying, and experiences of bullying are not associated with sex.